Purchasing and supply chain management - Monczka, Robert M. (South-Western Cengage Learning, 2011)
This edition presents the most recent critical developments in the field as well as the impact of the recent recession and ongoing business uncertainty on today's supply chain. This leading author team draws from firsthand experience and their relationships with executives and practitioners worldwide to present numerous cases, memorable examples, and unique insights that enable readers to better understand today's purchasing process.